2010
DOI: 10.1007/s00018-010-0591-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced cleavage of DNA topoisomerase I involves the cytoplasmic-nuclear shuttling of calpain 2

Abstract: Important to the function of calpains is temporal and spatial regulation of their proteolytic activity. Here, we demonstrate that cytoplasm-resident calpain 2 cleaves human nuclear topoisomerase I (hTOP1) via Ca(2+)-activated proteolysis and nucleoplasmic shuttling of proteases. This proteolysis of hTOP1 was induced by either ionomycin-caused Ca(2+) influx or addition of Ca(2+) in cellular extracts. Ca(2+) failed to induce hTOP1 proteolysis in calpain 2-knockdown cells. Moreover, calpain 2 cleaved hTOP1 in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
(93 reference statements)
1
10
0
Order By: Relevance
“…The results of the present study and previously published data in other models [24,35] suggest that CAPN1 might have different targets in the nuclear compartment of mammary gland cells during involution. Therefore we studied the possible role of CAPN1 in chromatin organization in whole mammary tissue.…”
Section: Capn1 Associates With Chromatin and Histone H3supporting
confidence: 76%
See 1 more Smart Citation
“…The results of the present study and previously published data in other models [24,35] suggest that CAPN1 might have different targets in the nuclear compartment of mammary gland cells during involution. Therefore we studied the possible role of CAPN1 in chromatin organization in whole mammary tissue.…”
Section: Capn1 Associates With Chromatin and Histone H3supporting
confidence: 76%
“…The calpain system has been reported previously to have a role in the nucleus of different cell types [14,23,24]. Since we have already demonstrated calpain translocation to the mitochondria and lysosomes during weaning, we investigated the possible role of these proteases in the nuclear compartment.…”
Section: Active Calpains Translocate To the Nucleus During Mammary Glmentioning
confidence: 96%
“…To verify the identity of the enzyme that cleaved nuclear Ku80, we treated the cells with calpeptin prior to treatment with 0.75 μM ionomycin since a previous study had reported that m -calpain was translocated from the cytosol to the nucleus after activation by calcium [ 24 ]. Calpeptin is a well-known, cell-permeable calpain inhibitor and synthetic peptidomimetic aldehyde moiety-conteining molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Although the induction of DNA damage is the main treatment for cancer, it can promote carcinogenesis by damaging normal cells, to which the majority of the adverse effects of anticancer therapy are attributed. Moreover, the DNA process is easily affected by cell cycle-related proteins and apoptosis regulators [ 23 , 24 ]; therefore, it is very important to control DNA damage and to repair it properly in order to minimize side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation